The role of adipokines in developmental programming: evidence from animal models. Issue 1 (July 2019) - Reynolds, Clare M; Vickers, Mark H
Abstract : Alterations in the environment during critical periods of development, including altered maternal nutrition, can increase the risk for the development of a range of metabolic, cardiovascular and reproductive disorders in offspring in adult life. Following the original epidemiological observations of David Barker that linked perturbed fetal growth to adult disease, a wide range of experimental animal models have provided empirical support for the developmental programming hypothesis. Although the mechanisms remain poorly defined, adipose tissue has been highlighted as playing a key role in the development of many disorders that manifest in later life. In particular, adipokines, including leptin and adiponectin, primarily secreted by adipose tissue, have now been shown to be important mediators of processes underpinning several phenotypic features associated with developmental programming including obesity, insulin sensitivity and reproductive disorders. Moreover, manipulation of adipokines in early life has provided for potential strategies to ameliorate or reverse the adverse sequalae that are associated with aberrant programming and provided insight into some of the mechanisms involved in the development of chronic disease across the lifecourse.